The influence of spectral power distribution on contrast sensitivity - Arranz, Isabel (2011)
The influence of lighting of different spectral power distribution on letter contrast sensitivity has been studied. The different spectral power distributions were obtained by filtering or dimming tungsten halogen lamps. Measurements were made on 20 young and healthy individuals (25 eyes) whose monocular contrast sensitivities were measured with a natural pupil. Sixteen combinations of test and surround luminance with high or low correlated colour temperatures were studied in such a way that the influence of test luminance, surround luminance or colour temperature of both visual fields could be independently studied. Both test luminance and surround luminance influenced contrast sensitivity but correlated colour temperature did not.